Diagnóstico e implementación de un medio alternativo de comunicación para las y los estudiantes del colegio Carmen Mora de Encalada del cantón Pasaje, periodo 2013. - Aguilar Márquez, Andrea Gisell (2015)
This thesis entitled, Diagnosis and implementation of an alternative means of communication for college students and Carmen Mora de Encalada Pasaje Canton, period 2013 is based on a process of diagnosis research - directed purpose to determine the benefits It generates the implementation of an alternative means of communication for college students and Carmen Mora de Encalada Pasaje Canton, period 2013.